Conhecimento de Docentes sobre Tecnologias da Informação e Comunicação (TIC) no Ensino Superior de Enfermagem em Santarém-Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Information and Communication Technologies (ICTs) stand out as important characteristics of contemporary society and foster transformations that are currently the target of diferente fields of research. Thus, the general objective of this study was to understand the use of Information and Communication Technologies (ICT) by teachers of the nursing course in private and public institutions of Santarem-Para. This is a field research with a qualitative and descriptive approach, carried out in three institutions of higher education in Santarem, through a semi-structured interview with 29 teachers of the nursing course. For the analysis of the data, we used the Bardin Content Analysis with emphasis on the thematic analysis. The results showed that for the interviewed teachers, the use of ICT as na educational resource contributed to the innovation process, since the technologies work as a means to facilitate the life of the human being, contribute to the process of teaching and learning, facilitating the approximation between theory and practice, helping to stimulate students' creativity, favoring the emergence of projects and advances in teaching and research. For the teachers in question, among the new roles of the higher education teacher in relation to ICT, are the facilitator and mediator in the teaching-learning process, adding the use of these technologies in their favor, besides acting as leaders in the projection in the educational environment. Among the main technologies used by teachers in this research are: datashow, cellular, television, computer, internet, virtual libraries, internet and whatsApp. This work can contribute to the nursing professors, so that they rethink the use of these technologies in the context of teaching and learning, favoring the application for pedagogical purposes. Although teachers recognize the importance of using ICTs and even work through them, more studies are needed on this use in health education, as well as programs and actions that favor and enhance the use of these technologies, especially in the undergraduate nursing course, the aim of this research. It can be seen, therefore, that there is a lack and demand of these studies and actions mainly in relation to institutions of the northern region of the Country.
Keywords: Tecnologias da Informação e Comunicação; Enfermagem; Ensino superior; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS; EDUCAÇÃO